A Chinese Christian Leader Revisited: The John Sung Papers at Yale Divinity Library. Issue 3 (1st October 2016) - Li, Tang; Smalley, Martha
ABSTRACT: John Sung (1901–1944) was a prominent Chinese Christian evangelist whose enduring influence is still recognized through China and Southeast Asia. His reputation has long been based primarily on his autobiography and excerpts from his diaries that his daughter Levi Sung selected and published. The correspondence, writings, and extensive diaries of Sung recently acquired by the Yale Divinity Library shed new light on his life and work. This article gives a detailed account of provenance, content, and format of all the materials included in the Sung papers. They are invaluable to the study and rediscovery of Sung's life, thought, and ministry as well as the history and development of indigenous Christianity and churches in China and Southeast Asia. This article also examines Sung's English diaries from the period of his hospitalization in a psychiatric facility to reveal complexities in Sung that have been less evident in published biographies and writings. Five additional original diary entries will be compared to their published versions to reveal alterations, deletions, and inaccuracies in the published extracts. The comparative study demonstrates that the diary extracts compiled by Levi, which are the most commonly-cited source on Sung, are in some cases problematic.